Tomorrow’s Digital Worker : A Critical Review and Agenda for Building Digital Competency Models - Polo, Federica; Kantola, Jussi (Springer, 2020)
In competency management studies, scholars call for the importance of digital savviness to hire, train, and develop new digital workers. Yet, the knowledge about the development of such a competence is still scarce. For this endeavor, we followed a systematic literature review to identify a sample of 103 published scientific articles and book chapters dealing with the development and implementation of competency tools in the past 10 years. To our surprise, our review suggests that the landscape of competency tools is surprisingly obsolete and that contemporary requirements of digitization have not yet been incorporated into updated usable competency tools. Through this review our hope is to provide competency managers and researchers with a framework to advance and upgrade their competency tools to address the gap between existing know how and the needed expertise of the digital world.
Keywords: Competency models; Competency tools; Digital competencies; Digitization; Digital worker; Systematic review; fi=Tuotantotalous|en=Industrial Management|